Improving Learning Achievement Through a Self-Esteem Perspective: The Secret to Student Success - Yunita, Rossa; Sarajar, Dewita Karema (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
When children enter the education stage in secondary school, that is when children enter adolescence where they are looking for their identity by trying new things that they have not encountered before. At this stage the school environment will further develop their thinking patterns and further expand the child's social life. Low self-esteem in students results in them not believing that they are able to do what their parents and teachers expect of them. Low self-esteem, showing avoidant behavior. This study aims to explore the relationship between self-esteem and academic achievement among high school students in Muara Teweh. During adolescence, the school environment and self-esteem play crucial roles in shaping students' identities and academic performance. Previous research has highlighted that low self-esteem can hinder optimal academic achievement. Through a survey of 60 high school students, data were collected using questionnaires to measure self-esteem and academic performance. The results indicate a relationship between self-esteem and academic achievement, although the correlation between them tends to be weak. These findings underscore the importance of attention to both variables in the educational context. Schools and educational communities are encouraged to pay attention to the complex dynamics between self-esteem and academic achievement to create a supportive learning environment for students' development. Students are also encouraged to strengthen their self-confidence in understanding subject matter and taking on new challenges. The implication of this research is that it can be a learning medium and consideration in making policies in the field of education. It is necessary to pay attention to the contribution of other variables in supporting and encouraging student academic achievement at school, such as self-efficacy variables and student learning independence.Saat anak memasuki tahap pendidikan di sekolah menengah, saat itulah anak memasuki masa remaja dimana mereka sedang mencari jati dirinya dengan mencoba hal-hal baru yang belum ditemui sebelumnya. Pada tahap ini lingkungan sekolah akan lebih mengembangkan pola pikir mereka dan lebih memperluas kehidupan sosial anak. Rendahnya self esteem pada diri siswa/i mengakibatkan mereka tidak percaya bahwa mereka mampu melakukan apa yang diharapkan orangtua dan guru kepada mereka. Rendahnya self esteem, memperlihatkan perilaku menghindar. Penelitian ini bertujuan untuk mengeksplorasi hubungan antara self-esteem dan prestasi belajar siswa SMA di Muara Teweh. Dalam tahap remaja, lingkungan sekolah dan kepuasan harga diri memainkan peran penting dalam pembentukan identitas diri dan prestasi belajar siswa. Penelitian sebelumnya menyoroti bahwa self-esteem yang rendah dapat menjadi hambatan dalam pencapaian prestasi belajar yang optimal. Melalui survei terhadap 60 siswa SMA, data dikumpulkan menggunakan angket untuk mengukur self-esteem dan prestasi belajar. Hasil menunjukkan adanya hubungan antara self-esteem dan prestasi belajar, meskipun korelasi antara keduanya cenderung lemah. Temuan ini menggarisbawahi pentingnya perhatian terhadap kedua variabel ini dalam konteks pendidikan. Sekolah dan komunitas pendidikan diharapkan dapat memperhatikan dinamika kompleks antara self-esteem dan prestasi belajar untuk menciptakan lingkungan pendidikan yang mendukung perkembangan siswa. Siswa juga didorong untuk memperkuat keyakinan diri mereka dalam memahami materi pelajaran dan mengambil tantangan baru. Implikasi dari penerlitian ini yaitu dapat menjadi media pembelajaran dan pertimbangan dalam mengambil kebijakan dalam bidang pendidikan. Perlu diperhatikan kontribusi variabel lainnya dalam mendukung dan mendorong prestasi akademik siswa di sekolah seperti variabel self efficacy dan kemandirian belajar pada siswa.